2015
DOI: 10.1080/09583157.2015.1099148
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among vegetable-infesting aphids, the fungal pathogenMetarhizium anisopliae(Ascomycota: Hypocreales) and the predatory coccinellidCheilomenes lunata(Coleoptera: Coccinellidae)

Abstract: Interactions among vegetable infesting aphids, the fungal pathogen Metarhizium anisopliae (Ascomycota: Hypocreales) and the predatory coccinellid Cheilomenes lunata (Coleoptera: Coccinellidae) AbstractEntomopathogenic fungi are among biocontrol agents being considered for the control of aphids on a variety of crops. Predatory coccinellids, although generalist, are also among important natural enemies that must be conserved for aphid management.Laboratory studies were carried out to investigate interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In previous studies, M. anispoliae has been shown to have minimal negative impacts on natural enemies (Zimmermann, ). Bayissa et al () also demonstrated the low toxicity of ICIPE 62 to the predatory coccinellid Cheilomenes lunata Fabricius, 1775; Coleoptera: Coccinellidae) under laboratory conditions, while Mweke, Ulrichs, Fiaboe, Maniania, and Ekesi () previously reported the non‐target effect of ICIPE 62 to natural enemies of aphids under field conditions. This non‐target effect presents an advantage of ICIPE 62 as a potential candidate for biopesticide development and commercialization against A. craccivora , since it is considered as one of the key criteria used in registration of biopesticide (Goettel, ; Goettel & Hajek, ; Montesinos, ).…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies, M. anispoliae has been shown to have minimal negative impacts on natural enemies (Zimmermann, ). Bayissa et al () also demonstrated the low toxicity of ICIPE 62 to the predatory coccinellid Cheilomenes lunata Fabricius, 1775; Coleoptera: Coccinellidae) under laboratory conditions, while Mweke, Ulrichs, Fiaboe, Maniania, and Ekesi () previously reported the non‐target effect of ICIPE 62 to natural enemies of aphids under field conditions. This non‐target effect presents an advantage of ICIPE 62 as a potential candidate for biopesticide development and commercialization against A. craccivora , since it is considered as one of the key criteria used in registration of biopesticide (Goettel, ; Goettel & Hajek, ; Montesinos, ).…”
Section: Discussionmentioning
confidence: 95%
“…96 Predatory coccinellids, Cheilomenes lunata were found to avoid feeding on aphids infected with entomopathogenic fungi, while foraging adult of C. lunata enhanced spread of M. anisopliae conidia between aphids which demonstrated the compatibility between the control agents. 78 With the exception of spiders, application of M. anisopliae was highly compatible with non-target organisms in onion fields as compared to dimethoate-treated plots. 97 Efficacy of entomopathogenic fungi (EPFs) varies with the resistance levels of host plants on which they are applied.…”
Section: Integrating Entomopathogenic Fungi As a Component In Sustainmentioning
confidence: 91%
“…Soil application of M. anisopliae for management of fruit flies was found to have no adverse effects on non‐target natural enemies, as compared to insecticide‐treated soils where no parasitoids emerged . Predatory coccinellids, Cheilomenes lunata were found to avoid feeding on aphids infected with entomopathogenic fungi, while foraging adult of C. lunata enhanced spread of M. anisopliae conidia between aphids which demonstrated the compatibility between the control agents . With the exception of spiders, application of M. anisopliae was highly compatible with non‐target organisms in onion fields as compared to dimethoate‐treated plots …”
Section: Entomopathogenic Fungi In Pest Managementmentioning
confidence: 95%
“…Studies about interactions between entomopathogenic fungi and other natural enemies (parasitoids and predators) have been performed worldwide (Roy et al 2006;Ormond et al 2011;Martins et al 2014;Bayissa et al 2016). However, there is very little information about interactions with other natural enemies in Coccinellidae species in general and E. connexa in particular.…”
Section: Discussionmentioning
confidence: 99%
“…(Ascomycota: Hypocreales). In contrast, Bayissa et al (2016) demonstrated that the compatibility between Metarhizium anisopliae (Metchnikoff) Sorokin (1883) (Ascomycota: Hypocreales) and the predator Cheilomenes lunata (Fabricius) (Coleoptera: Coccinellidae), could provide a sustainable strategy for effective management of aphids on crucifers.…”
Section: Introductionmentioning
confidence: 99%